Transport planning & traffic safety making cities, roads, & vehicles safer - Tiwari, Geetam; Mohan, Dinesh (CRC Press Taylor & Francis Group, 2016)
The book is interdisciplinary and aimed at professionals-traffic and road engineers, vehicle designers, law enforcers, and transport planners. The authors examine trends in performance of OECD countries and highlight the public health and systems approach of traffic safety with the vulnerable road user in focus